2016
DOI: 10.1177/0733464815581484
|View full text |Cite
|
Sign up to set email alerts
|

Association of Filial Responsibility, Ethnicity, and Acculturation Among Japanese American Family Caregivers of Older Adults

Abstract: Challenges of filial caregiving practices by 1st-generation immigrants due to differences in caregiving values between their home and host countries are well documented. This study explored the filial responsibility of later generation Japanese American caregivers of older adults. Acculturation and filial responsibility were measured using the Suinn-Lew Asian Self Identity Acculturation scale and Filial Values Index, respectively. A qualitative interview guide was developed using Gordon’s assimilation theory, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…In our study, the percentages of non-Hispanic black baby boomer caregivers (11.2%) and noncaregivers (10.5%) were similar ( P = .25), but the percentages of caregivers were smaller than the percentages of noncaregivers among Hispanic (8.6% vs 12.6%; P < .001) and Asian or Pacific Islander (1.1% vs 4.1%; P < .001) baby boomers. The results of our study support the idea that caregiving responsibilities may be shared among family members, as many African American, Hispanic, and Asian families do ( 26 , 27 ). Although some Hispanic and Asian baby boomers are providing assistance to aging persons, they might not consider themselves as caregivers because caring for their parents is perceived as normal and expected in their cultures.…”
Section: Discussionsupporting
confidence: 83%
“…In our study, the percentages of non-Hispanic black baby boomer caregivers (11.2%) and noncaregivers (10.5%) were similar ( P = .25), but the percentages of caregivers were smaller than the percentages of noncaregivers among Hispanic (8.6% vs 12.6%; P < .001) and Asian or Pacific Islander (1.1% vs 4.1%; P < .001) baby boomers. The results of our study support the idea that caregiving responsibilities may be shared among family members, as many African American, Hispanic, and Asian families do ( 26 , 27 ). Although some Hispanic and Asian baby boomers are providing assistance to aging persons, they might not consider themselves as caregivers because caring for their parents is perceived as normal and expected in their cultures.…”
Section: Discussionsupporting
confidence: 83%
“…More recently immigrated Asian caregivers (e.g., Filipino, Korean and Vietnamese caregivers) tend to experience greater acculturation and assimilation challenges compared to a later generation counterparts (e.g., 2nd and 3rd generation Japanese-American caregivers). More acculturated caregivers are open to the idea of using formal caregiver services (Young et al 2002) as an alternative way of fulfilling filial piety; however, caregivers' persistent, passed-on sense of the cultural value of filial responsibility are also found among later generations of Japanese-American caregivers (Kobayashi and Funk 2010;Miyawaki 2015b). …”
Section: Caregiving Attitudes Of Asian American Caregivers Of Older Amentioning
confidence: 99%
“…(22) In contrast, a study with Japanese immigrants revealed that institutionalization is well accepted both by the children and by the parents. (23) These findings demonstrate that, in Brazilian culture, moral aspects and social norms of filial responsibility are present in the care of parents, it being understood that institutionalization was considered by many an act of abandonment and that children feel responsible for caring for their parents. It is noteworthy that, although attitudes of filial responsibility are not associated with care behaviors (help in BADLs and IADLs), there were divergent results in the category "Difficulty in being a caregiving child".…”
Section: Discussionmentioning
confidence: 85%